Comparison of outcome of milwaukee regimen and 48 hours regimen in diabetic ketoacidosis in a tertiary care hospital in Chitradurga, Karnataka, India - P., Basavanthappa S.; V., Srinivasa; T., Sivachand (International Journal of Contemporary Pediatrics, 2020)
Background: Diabetic ketoacidosis (DKA) is an acute life threatening and a medical emergency that accounts for the majority of diabetes related mortality and morbidity in the pediatric age group who are suffering from type 1 Diabetes Mellitus (DM). Objective of this study was to compare the clinical outcome in a patient with DKA who are been treated with Milwaukee regimen (24hours) and 48 hours regimen. Methods: A retrospective study was conducted in PICU of tertiary care hospital in Chitradurga, Karnataka. Data was collected from 2015 to May 2018. Diagnosis of DKA was made by plasma glucose level higher than 200mg/dl, venous blood PH of <7.3 and /or bicarbonate <15 mmol/L, presence of ketonuria. Among 56 cases, 36 cases were treated with 48 hours regimen and 20 cases were treated with Milwaukee regimen and results were compared. Results: The median age of presentation was 7.52 years (Range: 2-14 years) with female: male ratio of 1:1.3. Newly diagnosed type 1 DM cases constituted 80.7%. The most common presenting complaints were hurried breathing and altered sensorium. The average length of stay in the ICU was 3.5 days for 48 hours regimen and 4.5 days for Milwaukee regimen. The mortality rate was 10.71 % (6 cases), among which 15% (3 cases) were patients treated with Milwaukee and 8.3% (3 cases) were patients treated with 48 hours regimen. Cerebral edema was found to be the commonest cause of fatality. Conclusions: There is lack of awareness regarding dog bite and its management among the rural population.